The Impact of Using Digital Video Recordings by Prospective Teachers on Their Technological Pedagogical Content Knowledge - Shaheen Shayeb; Wajeeh Daher (MDPI AG, 2024)
Analyzing digital video recordings (DVRs) is an effective instructional strategy for professionally preparing and developing prospective teachers. This study examines the impact of using DVRs among prospective teachers at Al-Qasimi College on their technological pedagogical content knowledge (TPACK) and its seven domains (TK, PK, CK, PCK, TCK, TPK, TPACK). The study was based on a mixed methodology approach, and the study sample included 70 prospective teachers who were distributed into an experimental group and a control group. Data were collected using the TPACK questionnaire and semi-structured interviews with 10 participants. The quantitative and qualitative results showed that prospective teachers in the experimental group significantly and positively impacted TPACK and its seven domains. The results of the study indicated that digital video recordings allowed prospective teachers to reflect and ponder on their teaching skills, content delivery, and the appropriate use of technology and its relevant tools in the educational process to identify strengths for development and weaknesses for improvement. Therefore, the results of the current study provide concrete evidence for the need to use DVRs as a promising educational approach in future professional preparation and to develop prospective teachers' technological pedagogical content knowledge (TPACK).